1990
DOI: 10.1111/j.1476-5381.1990.tb14143.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of 5‐hydroxytryptamine on penile erectile function in the rat

Abstract: 1 An increase in corporal pressure was elicited in pithed rats by stimulation of the sacral part of the spinal cord. This response was inhibited by intravenous injection of 5-hydroxytryptamine (5-HT) (ED50 = 28.5 + 2.2pgkg-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Thus, 8-OH-DPAT, which facilitates the ejaculatory behaviour, inhibits penile erections (Mathes et al, 1990;Finberg & Vardi, 1990). Furthermore, the non-selective 5-HT 1B receptor agonist 1-(3'-chlorophenyl)-piperazine (mCPP) induces penile erections (Berendsen & Broekkamp, 1987, c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 8-OH-DPAT, which facilitates the ejaculatory behaviour, inhibits penile erections (Mathes et al, 1990;Finberg & Vardi, 1990). Furthermore, the non-selective 5-HT 1B receptor agonist 1-(3'-chlorophenyl)-piperazine (mCPP) induces penile erections (Berendsen & Broekkamp, 1987, c.f.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of peripheral 5-HT receptors is less well established. Finberg and Vardi (1990) demonstrated an in vivo 5-HT-mediated inhibitory action on penile erection in rats as a result of vasoconstriction of the cavernosal arteries. In addition, Esen et al (1997) showed that the in vitro 5-HT-mediated contractile response in human penile veins was augmented in patients with venoocclusive disease.…”
Section: F Serotoninmentioning
confidence: 99%
“…7 Serotonin, by a peripheral mechanism, exerts an inhibitory action on penile erection through the activation of 5-HT 1D type of receptor. 12 On the other hand, p-chloroamphetamine (5-HT releasing agent) causes penile erection and ejaculation in anesthetized rats, which is limited to the lower spinal cord and/or peripheral sites. 13 Therefore, there is a difference in the peripheral action of 5-HT when comparing in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%